The effects of simulated gastric acid on the mechanical, optical, and physicochemical properties of different esthetic CAD-CAM materials - Basol, Ece Ucar; Dogan, Ilgin; Egilmez, Ferhan; Lassila, Lippo; Cekic-Nagas, Isil (Elsevier, 2026)
​​​​​​​Purpose: To investigate the effects of coffee and orange juice on 3 different esthetic ceramic materials regarding color changes, Vickers microhardness, and solubility & sorption changes among patients with reflux.
Methods: A glass-ceramic material (IPS Emax CAD), a polymer-infiltrated ceramic material (Vita Enamic), and a nano-hybrid ceramic material (Cerasmart) were selected for this study (n=32/group). Following the polishing procedure, all the samples were immersed in artificial saliva for 21 days. Half the samples were assigned to the control group and exposed only to artificial saliva (pH 7.3). The remaining 16 samples were exposed to saliva or simulated gastric acid. Sixteen samples from each group were exposed to gastric acid 3 times daily for 30 seconds. The color, Vickers microhardness, and solubility & sorption were then measured. Following this procedure, the samples were exposed to coffee and orange juice (n=8/per group). The samples were exposed to the solutions for 16 hours and 48 minutes to simulate 21 days of consumption. Final measurements were then obtained. Statistical significance was determined using Levene’s test to compare variances, and three-way analysis of variance (ANOVA) followed by Tukey’s post-hoc test, Welch’s ANOVA, and Games–Howell’s test were applied to reveal differences between groups.
Results: According to ANOVA, restorative material type and immersion media had a significant effect on color change (P < 0.001), microhardness (P < 0.001), and solubility & sorption (P < 0.001).
Conclusions: The choice of material is crucial for erosion-prone patients.